Human Decidual Stromal Cells in Early Pregnancy Induce Functional Re-Programming of Monocyte-Derived Dendritic Cells via Crosstalk Between G-CSF and IL-1β - Shao, Qianqian; Liu, Xin; Huang, Yufei; Chen, Xi; Wang, Huayang (Frontiers in Immunology, 2020)
Accumulation of dendritic cells (DCs) is a special characteristic of the decidual microenvironment. Decidua-infiltrated DCs show unique phenotypes and functions that promote the establishment of fetal-maternal tolerance. However, the regulatory mechanisms yet to be fully investigated. Decidual stromal cells (DSCs) are the major cellular component of decidua tissue. The interactions between DSCs and decidua-infiltrated immunocytes dictate immune tolerance in early pregnancy. Therefore, in the present study, we explore the effect of early pregnancy DSCs on monocyte-derived DCs and the relevant mechanisms. DSC-conditioned DCs showed altered phenotypes, secretion profiles and Th2 priming potential. G-CSF concentration was significantly up-regulated in the co-culture supernatant between DSCs and DCs. Supplementation of G-CSF neutralizing antibody partly reversed the reprogramming of DCs mediated by DSCs. Furthermore, G-CSF production was promoted by IL-1β, which was mainly produced by DCs and significantly up-regulated after their cultivation with DSCs. Interestingly, the effects of DSC on IL-1β production of DCs occurred in their immature stage but not their mature stage. Lastly, no significant difference of G-CSF was found in DSCs from healthy early pregnancy women and spontaneous abortions (SA) patients. However, DSCs from SA patients secreted less G-CSF in response to exogenous rhIL-1β or DC cultivation. In conclusion, our study bolster the understanding of the decidual immunomodulatory microenvironment during early pregnancy, and brings new insight into the potential clinical value of G-CSF in pregnancy disorders.